Sensory Profile, Water Content, Fat Content and Antioxidant Activity of Pecel Sauce with Black Garlic Addition - Rochmah, Alfi Nur; Ningrum, Widya Rafika; Zulfa, Fitriyah; Rukmakharisma, Prajwalita; Abdi, Yenny Febriana Ramadhan; Mulyani, Rizka; Adi, Prakoso; Suleman, Dininurilmi Putri; Nadhilah, Dini; Widyastuti, Retno (Journal of Food and Agricultural Product, 2025)
Pecel sauce is made using peanuts and has a spicy and sweet taste. The ingredients for making pecel sauce can be innovated by adding black garlics. Black garlic is garlic that can be processed at a temperature of 600-800C for several days and has a higher antioxidant potential than garlic. Antioxidant activity is a compound that can inhibit free radical reactions. Apart from having antioxidant potential, black garlic has distinctive flavor compounds. The aim of this research is to determine the use of black garlic in pecel sauce on the sensory acceptability of pecel sauce, its chemical characteristics and antioxidant potential.In this research, black garlic was added to other ingredients and ground together. This research on pecel sauce with the addition of black garlic used a Completely Randomized Design with a formulation of adding black garlic to the pecel sauce at 4%, 8%, 12% and 18%. The results of the research showed the sensory acceptance of pecel chili sauce with the addition of black garlic. Sensory pecel chili sauce with the addition of black garlic based on the parameters of aroma, taste, texture, overall the panelists liked making pecel chili sauce with the addition of black garlic by 4%. The results of the analysis of the chemical content of pecel chili sauce with the addition of 4% black garlic had a water content of 12.52%, a fat content of 17.97% and an antioxidant activity value of 31.8%. Key word: antioxidant, black garlic, pecel sauce, sensory